Twin reciprocal embryo transfer between alpacas and llamas - Huanca Mamani, Teodosio; Sumar, Julio; Naveros Flores, Mary Luz; Cárdenas Minaya, Oscar; Gonzáles Castillo, Mario Lino; Mamani Cato, Rubén Herberht (Instituto Nacional de Innovación Agraria. Universidad Nacional Mayor de San Marcos, 2020)
4 Páginas